Pretreatment Reversal Reaction in Borderline Tuberculoid Leprosy Presenting as a Unilateral Anesthetic Plaque on the Dorsum of the Foot: A Case Report - Juliandra Firdaus; Khufitha Tasya; Randy Nugraha (The ASEAN Journal of Military and Preventive Medicine, 2026)
Background: Leprosy is a chronic infectious disease caused by Mycobacterium leprae, primarily affecting the skin and peripheral nerves. Type 1 leprosy reaction, also known as reversal reaction, is an acute immunological event commonly observed in borderline forms of leprosy. Although reversal reactions frequently occur during treatment, they may also develop before the initiation of multidrug therapy. Early recognition is essential to prevent nerve damage and disability. This report describes a case of borderline tuberculoid leprosy with a pretreatment reversal reaction and peripheral nerve involvement. Case illustration: A 50-year-old woman presented with progressive redness on the dorsum of the left foot for one week, accompanied by pain and numbness persisting for one month. The lesion initially appeared as a small hypopigmented patch one year earlier, subsequently enlarging and becoming elevated, erythematous, warm, and painful. Dermatological examination revealed unilateral, well-defined erythematous anesthetic plaques on the dorsum of the left foot and toes. Neurological assessment demonstrated enlargement of the left common peroneal nerve, impaired pain and touch sensation, and reduced motor strength. Slit-skin smear examination was negative, with a bacterial index of 0/3. Discussion: The clinical findings supported a diagnosis of borderline tuberculoid leprosy with a pretreatment reversal reaction. A negative slit-skin smear was consistent with paucibacillary disease. Early initiation of corticosteroid therapy was essential for controlling inflammation and preventing irreversible nerve impairment. Conclusion: Pretreatment reversal reaction should be considered in patients with borderline tuberculoid leprosy, even before the initiation of multidrug therapy. Early recognition and prompt corticosteroid treatment are essential to prevent irreversible nerve damage.